A educação moral construtivista e suas contradições: uma leitura critica - Garcia, Diogo Alfonso [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research presents as goal a critical analysis of the concept of cooperation from the book The Moral Judgment in Children of Jean Piaget, and practical applications for moral education developed from this concept. We find that these applications incorporate to the field of moral education instrumental rationality and thus may result in conservative moralizing techniques, refuting some critical possibilities that perhaps had the Piagetian concept of moral judgment. The work uses as a theoretical reference the Critical Theory of Society, in particular some works of Adorno and Horkheimer. Among the contradictions identified on constructivist proposals stands out the instrumentalization of moral education, proposed by Kohlberg from the Piagetian framework, which results in moral education techniques and reducing the morality of the problem to a question of individual development. We consider the relationship between morality and respect for the law as an essentially contradictory relationship, since Piaget assumes that there can be a harmonious relationship between the individual and the rules in capitalist society. The theoretical proposition of the authors of the Frankfurt School in the field of morality is to make the subject aware of the contradictions of morality, as well as make you aware of the ways in which contradictions are expressed in their subjectivity. From the Critical Theory, admit that contradictions should be disclosed, and the contents of the social order, and this would result in a moral education proposal widely different from Piaget

Esta pesquisa apresenta como objetivo uma análise crítica do conceito de cooperação a partir do livro O Juízo Moral na Criança de Jean Piaget, e das aplicações práticas para a educação moral desenvolvidas a partir deste conceito. Verificamos que essas aplicações incorporam ao campo da educação moral a racionalidade instrumental e, dessa forma, podem resultar em técnicas de moralização conservadora, refutando algumas possibilidades críticas que porventura houvessem no conceito piagetiano de juízo moral. O trabalho utiliza como referencial teórico a Teoria Crítica da Sociedade, em especial algumas obras de Adorno e Horkheimer. Entre as contradições que identificamos nas propostas construtivistas destaca-se uma instrumentalização da educação moral, proposta por Kohlberg a partir do referencial piagetiano, que resulta em técnicas de educação moral e na redução do problema da moralidade a uma questão do desenvolvimento individual. Consideramos a relação entre a moralidade e o respeito à lei como uma relação essencialmente contraditória, pois Piaget supõe que possa existir uma relação harmoniosa entre o indivíduo e as regras na sociedade capitalista. A proposição teórica dos autores da Escola de Frankfurt no campo da moralidade é tornar o sujeito consciente das contradições da moralidade, assim como torná-lo consciente das formas como as contradições se expressam em sua subjetividade. Partindo da Teoria Crítica, admitimos que as contradições devem ser reveladas, assim como o conteúdo da ordem social, e disto resultaria uma proposta de educação moral amplamente diversa da piagetiana
Keywords: Educação moral; Teoria crítica; Autonomia nas crianças; Construtivismo (Educação); Moral education